Empowerment of Disease Control at District level for the Effective Disease Prevention and Control: Case of Muang District, Yasothon Province - รัตนแสง, พงษ์สวัสดิ์ (Disease Control Journal, 2012)
This study aimed to develop the process of the empowerment of disease control at district level towards to decrease the burden of Dengue hemorrhagic fever (DHF) and Tuberculosis(TB) in Muang District, Yasothon Province. The data was collected from the health personnel involving disease surveillance and control and the persons who response on disease surveillance and control in community by using the questionnaires, knowledge and participation assessment form and the empowerment of disease control at district level assessment form. The quantitative data was analyzed by using percentage, means and standard deviations and Paired t-test while the content analysis was used for the qualitative data. The results revealed that before implementation, DHF and TB had been increasing. The process of participation of network in district was not established while the prevention and disease control activities were planed and performed by health personnel only. The surveillance system as the coverage and timeliness of disease report was under the standard. This study developed and strengthened the process of the empowerment of disease control at district level in 4 systems: 1) the administration system 2) participatory social network 3) the surveillance and response system and 4) the prevention and control innovation by community. This implementation affected to reduction of DHF incidence from 98.38 to 24.59/100,000 population, and 99.1 °/o of TB patients received medication from village health volunteers, so that success rate in treatment was increased. The participation of communities and network organizations in district was the key of success in this implementation and this should be shared to learn and applied to carried out in the other areas.